Key success factors of information systems security - Arbanas, Krunoslav (Array, 2019)
The issue of information systems security, and thus information as key resource in today's information society, is something that all organizations in all sectors face in one way or another. To ensure that information remain secure, many organizations have implemented a continuous, structured and systematic security approach to manage and protect an organization's information from undermining individuals by establishing security policies, processes, procedures, and information security organizational structures. However, despite this, security threats, incidents, vulnerabilities and risks are still raging in many organizations. One of the main causes of this problem is poor understanding of information systems security key success factors. Identifying and understanding of information security key success factors can help organizations to manage how to focus limited resources on those elements that really impact on success, therefore saving time and money and creating added value and further enabling operational business. This research, based on comprehensive literature review, summarizes most cited key success factors of information systems security identified in scientific articles indexed in relevant databases, of which the top three success factors were management support, information security policy and information security education, training and awareness. At the end, article states identified research gaps and provides readers with possible directions for further researches.